Wind load effect to the ratio cover structure - Mohd Erie Adnin, Zamri (2014)
Structural damage due to wind storm is often occurred in Malaysia. Base on previous study conducted, non-engineering Structures are simply to fail due to wind load. One of the common non-engineering structures is patio or always be identify as awning. This type of structure is commonly used as additional extension to Malaysian building system for several purposes. The information related to this type of structure due to wind load is very rare. Therefore, further understanding of the wind load impact to patio need to be well understood before structural can be design to resist wind load. Therefore this study is conducted to identify the possibility of wind speed can caused the failure to the structure. Three type of dimension are used in this study which is 3m x 3m, 3m x 4.2m and 3m x 5,4m which are been identified as common size than widely used in Malaysia. Structural Design Software namely SAP 2000 are been used to examine the wind load effect to patio. From the result is shown that by minimum wind speed that cause possibility of failure to the patio structures is 16 m/s. Result also had shown that the distance between the trusses systems in patio structure need to be considered. Therefore the consideration of wind load design in patio structure need to be concern during construction stage. Further investigation need to be investigated in order to ensure the patio can able to withstand to wind load.